Can Picture Dictionaries Unlock Vocabulary Mastery? Unveiling Insights Through Quasi-Experimental Research - Menggo, Sebastianus; Amul, Armina; Ndiung, Sabina (Universitas Hamzanwadi, 2024)
The current study assessed the effectiveness of employing a Picture Dictionary to enhance the vocabulary acquisition of junior high school learners. A significant improvement in vocabulary comprehension was found to have been correlated with learners taking advantage of a visual dictionary compared to those who did not use such a resource. This idea points out that visual dictionaries could be a good option for students to enhance their vocabulary acquisition efforts. This research used a quasi-experimental design and the test as the research instrument to determine the students' vocabulary mastery. In this research, the test is the research instrument to determine the student's vocabulary mastery. This research has been conducted on seventh-grade students in the academic year 2022-2023 with a total sample of sixty respondents. A random sampling technique was employed to determine the group of respondents. The experimental and control groups' average scores differ, as determined by the data analysis. By comparison, the control group attained an average score of 61.7, but the group participating in the experiment attained a mean score 80. The average scores indicate that the group participating in the experiment achieved a mean score greater than the control class.